Damage Awards and Earnings Management in the Oil Industry - Hall, Steven C.; Stammerjohan, William W. (The Accounting Review, 1997)
[This paper examines the relationship between the incidence of litigation events with potentially large damage awards and managers' accounting choices. We argue that the size of damage awards is a function of reported net income and net worth, and that this relationship provides management an incentive to manipulate accounting numbers. Our results indicate that managers of oil firms facing potentially large damage awards choose income decreasing non-working capital accruals relative to managers of other oil firms. Further, the results indicate that the management of these firms makes accounting choices that result in lower non-working capital accruals during the litigation period than in other years. These negative non-working capital accruals appear to result from the under-estimation of new reserves.]